2008
DOI: 10.1108/14635770810854353
|View full text |Cite
|
Sign up to set email alerts
|

A study on the ISO 14000 certification and organizational performance of Indian manufacturing firms

Abstract: Purpose -The purpose of this paper is to identify the critical factors (CFs) of ISO 14000; to determine if ISO 14000 certification results in improved organizational performance; and to analyze the levels of and changes in these CFs and levels of and changes in the indicators of organizational performance (IOPs) in relation to firm attributes considered in the present study. Design/methodology/approach -The study employs questionnaire-survey approach to obtain the practitioners' perceptions of ISO 14000 certif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 22 publications
2
42
1
Order By: Relevance
“…The impacts on firms of the application of ISO 14001 have been deeply investigated by scholars. Recent works concerning benefits of ISO 14001 implementation are [27,[31][32][33][34][35][36][37][38][39][40][41]. Scholars also investigated barriers and constraints to ISO 14001 adoption and maintenance [25,27,30,33,34,37,39,[41][42][43][44][45].…”
Section: Previous Surveys On the Application Of Emas In European Firmsmentioning
confidence: 99%
“…The impacts on firms of the application of ISO 14001 have been deeply investigated by scholars. Recent works concerning benefits of ISO 14001 implementation are [27,[31][32][33][34][35][36][37][38][39][40][41]. Scholars also investigated barriers and constraints to ISO 14001 adoption and maintenance [25,27,30,33,34,37,39,[41][42][43][44][45].…”
Section: Previous Surveys On the Application Of Emas In European Firmsmentioning
confidence: 99%
“…Both, India's recently released 4th census report on MSMEs 1 (DCSME, 2009) and the 2011 ISO survey (ISO Survey, 2011) have documented a significant uptake in ISO14001 certifications among small and medium-sized Indian companies. This positive trend is somewhat surprising in that previous studies on environmental management systems in India have identified a number of obstacles affecting their uptake and effectiveness in Indian firms (Dasgupta, 2000;Padma et al, 2008;Qadir and Gorman, 2008). These obstacles include a lack of transparency, weak regulatory compliance and certification schemes and the large costs associated with 1 Enterprises in India are classified into micro, small and medium enterprises (MSMEs) based on their investment in plant and machinery (for manufacturing enterprises) or on equipment (for service providers) (see DCMSME, 2009, p.2).…”
mentioning
confidence: 70%
“…For cost is a key certification issue, unsurprisingly many studies found ISO uptake to occur primarily among larger firms with the requisite financial means (del Brio et al, 2001; Hillary, 2004; Khanna, 2010; Lagodimos et al, 2007;Nishitani, 2009). Also, larger and more experienced firms are seen to be more likely to achieve effective EMS implementation and to realize long-term benefits from ISO14001 certification (Padma et al, 2008).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations